RESOLUSI KONFLIK AGRARIA DI DESA KAMPAR KECAMATAN KAMPA KABUPATEN KAMPAR - Muhammad Rizki; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Kampar is one of the regencies having the greatest agrarian conflict in Riau province due to many palm oil plantations as an agricultural sector that result in the highest causing factor of agrarian conflict particularly in Riau province, generally in Indonesia. One of the conflicts that occurred in Kampar regency is the conflict between Tasma Puja Company and Kampar village society. It had happened for a long time because the society did not obtain the land compensation from the company. The solutions previously taken did not work and demanded the conflict resolution. This research study, therefore, aims at exploring the role of Kampar regency government in conflict resolution between Tasma Puja Company and Kampar village society. The concept used in this study was the theory of conflict resolution adapted from Fisher in terms of negotiation, mediation, and arbitration. This research was a case study in qualitative method utilizing snowball sampling with observation, interview, library study, and documentation as the techniques of collecting data. The results of study indicate that resolving conflicts only reaches the negotiation stage, and the mediation stage. Not until the arbitration stage. Negotiation have not been effective in dealing with conflicts and the mediation stage led by the regent of Kampar, bright spot was found and the company was willing to pay compensation for the society.. It is suggested that the local government should abrogate the status of the conflict and recover it after the conflict in order to have a good relationship between the two parties.Keywords : Resolution, Conflict, Land